Fungicidal activity of seeds of Abrus precatorius L., Datura metel L., and Diploknema butyracea (Roxb.) H.J. Lam against phytopathogenic fungi - Maharjan, Elina; Wong, Mui-Yun; Thapa, Umesh; Adhikari, Rameshwar; Joshi, Dev Raj (Scientific World, 2024)
This study aimed to investigate the antifungal activity of seeds of Abrus precatorius L., Datura metel L. and Diploknema butyracea (Roxb.) H.J. Lam against common phytopathogenic fungi. The powdered seeds were extracted by Soxhlet extraction method using methanol as a solvent. Antifungal activity was performed by poison agar technique with different concentrations ranging from 5 to 20% of seed extracts against two fungal pathogens - Fusarium oxysporum f. sp. cubense R4 (FocR4) and Rhizoctonia spp. Among three plant seed methanolic extracts at 5% concentration, D. metel seeds showed significant inhibition with 69.81±3.30% percentage inhibition of diameter growth (PIDG) against FocR4 on 8th day and 77.51±3.00% PIDG Rhizoctonia spp. on 5th day. All the plant seed extracts showed complete inhibition against mycelial growth at ≤10% concentration. UV-visible spectroscopy spectra showed the peaks at 238 nm and 280 nm wavelengths for the seed extracts of A. precatorius L., and D. metel L., respectively while D. butyracea (Roxb.) H.J. Lam showed the peaks at 206 nm and 262 nm. These peaks were assumed to represent the antifungal compounds. The antifungal activity of the plant extracts could be attributed by the phytochemicals present in crude seed extracts. Although further studies are necessary, our data indicate that seeds of the examined three plants are potential biofungicides which could substitute for chemical fungicides.